A PERANCANGAN BOARD GAME THE ADVENTURE TOWARDS CONFIDENCE BAGI ANAK 7-12 TAHUN UNTUK MENINGKATKAN KEPERCAYAAN DIRI - korompis, leonny (Jurnal Vicidi, 2024)
Self-confidence is an important thing but there are still many people who feel insecure. This is because from an early development age there is no media that can help someone grow their confidence. Creating media that can help foster selfconfidence from an early age with interactive media, namely board games. Seeing this, the purpose of this research is to create educational media board games that can increase their confidence in a fun way and have interesting visual elements and interactive challenges. This research uses literature and qualitative study methods to review related literature and interview the target market and someone who is an expert in this field. Data was obtained from international and national journals, then analyzed descriptively. Creating an effective and engaging solution to boost their confidence. It requires compelling visual elements and interactive challenges that can inspire and provide positive encouragement, so that they can overcome selfconfidence issues in a fun and rewarding way. The results of this study show that board games can be an effective medium to increase children's self-confidence. Board games that have engaging visual elements and interactive challenges can help children to learn about the importance of self-confidence and start developing it from an early age.